2014
DOI: 10.11114/jets.v2i3.399
|View full text |Cite
|
Sign up to set email alerts
|

Education for Developing a Global Omani Citizen: Current Practices and Challenges

Abstract: Oman is a developing country which reformed its educational system in 1998 in order to meet the challenges of the 21 st century, especially economic challenges. Strength of national identity and developing a sense of global citizenship were among the priorities of the new educational reform. This paper is based on a review of current practices regarding global citizenship education in educational system. The purpose of this theoretical study was to explore the current provision of the aspects of global citizen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 12 publications
1
15
0
1
Order By: Relevance
“…Instead, they regard it as part of their Islamic and national identity; as one participant directly highlighted, it is not a ‘Western concept that has come with the era of globalisation to threaten our national identity’. These results validated the results that were revealed by Al-Maamari (2014), who found that the educational system in Oman is not nationally centred, as it directs attention towards learning about global issues. In addition, the results also reflect the intention of SQU statements about graduate outcomes and the university’s strategic plan (2016–2020), both of which highlighted the importance of preparing the students for exercising GC obligations.…”
Section: Discussion Of the Findingssupporting
confidence: 88%
See 2 more Smart Citations
“…Instead, they regard it as part of their Islamic and national identity; as one participant directly highlighted, it is not a ‘Western concept that has come with the era of globalisation to threaten our national identity’. These results validated the results that were revealed by Al-Maamari (2014), who found that the educational system in Oman is not nationally centred, as it directs attention towards learning about global issues. In addition, the results also reflect the intention of SQU statements about graduate outcomes and the university’s strategic plan (2016–2020), both of which highlighted the importance of preparing the students for exercising GC obligations.…”
Section: Discussion Of the Findingssupporting
confidence: 88%
“…This result validated what was found by Hett (1993) and Stevens (2013) regarding the positive impact of GCE courses in shaping the students’ perspectives regarding world issues. Yet, it is not possible to attribute these positive perceptions to attendance of the course, as the participants also related their views to the nature of the political and social context that they belong to which is characterised by Al-Maamari (2014) as not totally nationalistic. Generally, the participants associate GC with the humanistic approach that raises a feeling of common humanity, as some researchers stated (Brunell, 2013; Osler and Starkey, 2005; UNESCO, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vatandaşlık eğitimi, dünya çapında farklı ekoller halinde uygulanmakta olup içerisinde birbirine benzer ancak farklılıklarla da karşılaşılabilecek dersleri barındırmaktadır (Shlapentokh, 1998;Ichilov, 1998;Hirsberg, 1998;Parmenter, 2008;Meihui, 2008;Gopinathan and Sharpe, 2008). Sosyal Bilgiler dersi de temel hedefi vatandaşlık eğitimi olan ve çoğunlukla da çokdisiplinli ya da disiplinlerarası program anlayışlarına uygun olarak meydana getirilen bir ders olarak pek çok ülkede okutulmaktadır (Boon and Sim, 2005;Açıkalın, 2011;Maamari, 2014). Dersin ortaya çıkışında kültürlerarası etkileşim kavramının etkili olduğu; 20. yüzyılın başlarında Amerika toplumunda ortaya çıkan, farklı kültürlere sahip insan gruplarının yoğun etkileşim ve birlikte yaşamaya başlama süreçlerini yönetmek adına bu derse ihtiyaç duyulduğu ifade edilebilir (Bining and Bining, 1941;Atwood, 1982).…”
Section: Introductionunclassified
“…found that carefully selecting global literature during read aloud time in an elementary school was associated with students "developing richer understandings of themselves as complex cultural beings, a deeper appreciation of others and diverse perspectives in the world, and a perception of themselves as capable problem-solvers who take action" (p. 617). In addition to relevant content, situated practice involves authentic inquiry-based learning experiences and collaborative learning opportunities for students to work together to construct knowledge in ways that build 21 st century skills(Al-Maamari, 2014;Lindsay & Davis, 2013;Spires, Chang, Bot, & Himes, 2015).…”
mentioning
confidence: 99%